Polish and Danish regulations on the search for portable antiquities ‒ remarks upon the recent amendment of the law in Poland - Artemiuk, Jakub (Folia Praehistorica Posnaniensia, 2024)
The Act of 13th July 2023 amending the Act on the Protection and Care of Monuments constitutes a radical change to the previously existing regulations concerning the search for portable antiquities in Poland using electronic or technical devices. The main modification is waiving the requirement to obtain permission from the Provincial Heritage Conservation Officer for an amateur search for portable antiquities, including archaeological finds. In its place, a system of reporting the surveys via a mobile application will be introduced. This paper compares the current and the new Polish regulations with the solutions successfully adopted in Denmark and analyses the effectiveness of the existing Polish regulations using the available statistical data and considering critical opinions.